PENGARUH DOSIS PUPUK ORGANIK PETROGANIK DAN MIKORIZA TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN JAGUNG MANIS (Zea Mays Saccharata) VARIETAS TALENTA - Minal Abidin; Sugeng Darwanto; Retno Dwi Andayani (Universitas Islam Kadiri, 2017)
Sweet corn provides high profit relative when cultivated properly (Sudarsana, 2000). One of the efforts that can be taken in producing quality sweet corn is the determination of the dose of organic fertilizer “Petroganik and proper biofertilizer. The alternative to resolve the problems of soil with low fertility is by way of utilization of arbuscularmycorrhiza fungi (CMA). This study purpose: 1) to know the interaction dose of organic fertilizer “Petroganik” and mikoriza on growth and production of sweet corn; 2) to know the effect of dose of organic fertilizer “Petroganik” and mikoriza on growth and production of sweet corn. The study was conducted in January - March 2017, in Kalen, Sidomulyo Village, District Wates, Kediri Regency. This study used a factorial randomized block design (RAK), consisting of two factors and three repetitive. The results of the study concluded that: 1) sweet corn was inoculated mycorrhiza fungi was not significantly different from the treatment combination with the addition of dose of “Petroganik” fertilizer; 2) on plant growth the overall treatment had no real effect and no interaction occurred.